A Novel Frameshift Mutation in SLC2A1 Associated with a Mild form of Glucose Transporter Type 1-Related Movement Disorder - Awaad, Yasser M.; Berry, Ian R.; Tomoum, Hoda Y.; Elsayed, Solaf M. (Journal of Pediatric Neurology, 2015)
The phenotypic spectrum of glucose transporter type 1 (GLUT1) deficiency syndrome is now known to be a continuum that includes the classic phenotype as well as atypical childhood absence epilepsy, myoclonic astatic epilepsy, and paroxysmal nonepileptic findings such as intermittent ataxia, choreoathetosis, dystonia, and alternating hemiplegia. We report the case of a mentally normal child with history of infantile seizures, which remitted but later developed nonepileptic movement disorder, responsive to carbohydrate intake, with a novel frameshift mutation (c.1344_1347delCTAC p.Y449fs) in the last exon of the GLUT1 gene. This case further broadens the phenotypic spectrum of GLUT1 deficiency syndrome. We provide evidence from this case and previous reports that mutations affecting the length and composition of the intracellular C-terminal domain of the GLUT1 protein have a variable and somewhat unpredictable range of pathological effects. These range from null phenotypes associated with C-terminal domain absence, to milder presentations associated with C-terminal domains comprising partially and (in this case study) completely abnormal amino acid sequences.
Keywords: GLUT1; glucose transporter; SLC2A1